Noun phrase in the generative perspective - Alexiadou, Artemis; Haegeman, Liliane M. V.; Stavrou, Melita (Berlin ; New York : Mouton de Gruyter, 2007)
The goal of this book is twofold. On the one hand we want to offer a discussion of some of the more important properties of the nominal projection, on the other hand we want to provide the reader with tools for syntactic analysis which apply to the struct.
The emergence and the structure of DP : articles and demonstratives -- Determinerless noun phrases -- DP-internal functional projections -- Adjectives in the DP : problems of distribution and interpretation -- Semi-functional categories : the N-of-N construction and the pseudo-partitive construction -- Argument structure in nominals -- Possessors and genitives -- Inalienable possessors.
Includes bibliographical references (pages 617-655) and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Grammar, Comparative and general -- Noun phrase; Grammar, Comparative and general -- Syntax; Syntagme nominal; Syntaxe; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax; Grammar, Comparative and general -- Noun phrase; Grammar, Comparative and general -- Syntax; Morphosyntax; Nominalphrase; Determinansphrase; Electronic books